2021
DOI: 10.3390/min11010046
|View full text |Cite
|
Sign up to set email alerts
|

Marble Waste Valorization through Alkali Activation

Abstract: In the present study, the valorization potential of marble waste in the presence of metakaolin via alkali activation was explored. The activating solution used consisted of NaOH and sodium silicate solutions. The effects of marble waste to metakaolin ratio, particle size of raw materials, curing temperature, and Na2O/SiO2 and H2O/Na2O molar ratios present in the activating solution on the main properties and the morphology of the produced alkali-activated materials (AAMs) was evaluated. The durability and stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The results showed that a 30 wt% incorporation of marble powder increased the fluidity of mortar by almost 22% but yielded an almost 20% decrease in compressive strength. Some studies suggest that the valorization of marble powder for synthesizing geopolymers is promising, but the development of mechanical and microstructural characteristics of geopolymers with marble powder needs further examination 54–57 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that a 30 wt% incorporation of marble powder increased the fluidity of mortar by almost 22% but yielded an almost 20% decrease in compressive strength. Some studies suggest that the valorization of marble powder for synthesizing geopolymers is promising, but the development of mechanical and microstructural characteristics of geopolymers with marble powder needs further examination 54–57 …”
Section: Introductionmentioning
confidence: 99%
“…54 However, combining marble powder with other aluminosilicates with high concentrations of Si and Al may improve the reactivity and geopolymerization. Very recently, Komnitsas et al 55 activated marble powder in conjunction with metakaolin, NaOH, and Na 2 SiO 3 , forming geopolymer. It is reported that incorporation of marble powder into the metakaolin-based geopolymer enables the formation of geopolymer with better physicomechanical properties, as well as contributing to the utilization of the waste and reducing the detrimental environmental effects of marble waste.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24], geopolymer composites were prepared with dolomite quarry dust using fly ash-based geopolymer. The properties of marble waste in connection with the metakaolin via alkali activation were also studied [25]. However, the comparison of five different WSP (feldspar, limestone, marlstone, dolomite, marble) has not been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they are either stored in warehouses for future use in other applications or disposed of in landfills, which can cause environmental issues. Some attempts have been done to use marble waste as a replacement of aggregates, additive in concrete production, and as well as starting material substitution of red clay up to 30 wt.% for the manufacturing of bricks [16][17][18][19]. It was found that the addition of marble waste can enhance the technological properties of manufacturing materials and contribute to significant economic and environmental benefits [16,20].…”
Section: Introductionmentioning
confidence: 99%